1997
DOI: 10.1016/s0092-8674(00)80361-x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Export Receptors: From Importin to Exportin

Abstract: The important conclusion is that the import receptors and Douglass J. Forbes for a number of the major nuclear localization pathways Department of Biology 0347 are becoming known (Figure 2, top). It is the clear expec-University of California at San Diego tation that additional receptors for other import path-La Jolla, California 92093 ways will also be found. Nuclear ExportRNAs exit the nucleus through the nuclear pore. Elegant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
184
1
2

Year Published

1998
1998
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(192 citation statements)
references
References 21 publications
5
184
1
2
Order By: Relevance
“…Finally, the presence of the N G , N G -dimethylarginine could help determine the localization of the modified protein (Pintucci et al 1996) as demonstrated here. For instance, it could be mediating interactions of hnRNPs with the nuclear export machinery (Ullman et al 1997).…”
Section: Protein Methylation and Nuclear Export Genes And Development 685mentioning
confidence: 99%
“…Finally, the presence of the N G , N G -dimethylarginine could help determine the localization of the modified protein (Pintucci et al 1996) as demonstrated here. For instance, it could be mediating interactions of hnRNPs with the nuclear export machinery (Ullman et al 1997).…”
Section: Protein Methylation and Nuclear Export Genes And Development 685mentioning
confidence: 99%
“…Because Ran GAP is localized in the cytoplasm and the Ran guanine nucleotide exchange factor (GEF) RCC1 is located in the nucleus, a model has been proposed whereby RanGTP in the nucleus stimulates the formation of Crm1/NES complexes leading to nuclear export. Upon translocation into the cytoplasm, Crm1/ NES complexes are dissociated in the presence of RanGDP (for review, see Ullman et al 1997). This has led to the suggestion that ERK is retained in the cytoplasm by association with its activator, MEK, and that dissociation from MEK leads to its nuclear accumulation.…”
Section: How Does the Mapk Go Nuclear?mentioning
confidence: 99%
“…The poly(A) tail serves different purposes for mRNAs on their way to being translated into protein+ Polyadenylation is thought to be necessary for efficient export of mRNA from the nucleus (Ullman et al+, 1997;Hilleren et al+, 2001) and plays a role in the maintenance of mRNA stability in the cytoplasm (Decker & Parker, 1993;Brown & Sachs, 1998)+ Moreover, efficient mRNA translation also requires a poly(A) tail (Gallie, 1991;Iizuka et al+, 1994;+ Lack of a poly(A) tail can, therefore, result in unstable poorly translated mRNA and reduced amounts of gene product+…”
Section: Introductionmentioning
confidence: 99%